Synthesis of reversible circuits with minimal costs - Yang, Guowu; Song, Xiaoyu; Hung, William N. N.; Perkowski, Marek A.; Seo, Chang-Jun (Calcolo, 2008)
We present fast algorithms to synthesize exact minimal reversible circuits for various types of gate and cost. By reducing reversible logic synthesis problems to permutation group problems, we use the powerful algebraic software GAP to solve such problems. Our approach can minimize for arbitrary cost functions of gates. In addition, we show that Peres gates are a better choice than the standard Toffoli gates in libraries of universal reversible gates.